How Music Works: the science and psychology of beautiful sounds, from Beethoven to the Beatles and beyond - Powell, John 1955- (Little, Brown and Company, 2010)
What makes a musical note different from any other sound? How can you tell if you have perfect pitch? Why do 10 violins sound only twice as loud as one? Do your Bob Dylan albums sound better on CD or vinyl? In a clear, accessible, and engaging voice, Powell explores the science and psychology behind music. The perfect gift for music lovers everywhere. This edition also includes a CD of examples and exercises from the book.